Kajian Literatur: Penggunaan Media Sosial Sebagai Sarana Dalam Meningkatkan Pembelajaran Pendidikan Agama Islam Pada Generasi Muda - Yulianti, Putri; Riadi, Akhmad; Zahratunnisa, Fadia; Aulia Amanda Fatimah, Nur; Arrahima, Aulia (Indonesian Journal of Islamic Education, 2024)
In today's digital era, the main challenge for the younger generation is to ensure that Islamic religious education remains relevant and useful in the face of the rapid development of Information Technology and social media. The use of social media has a role as a means to improve PAI learning in the younger generation. The influence of social media on how individuals understand and practice religious teachings is due to the increasing access of the younger generation to Islamic religious content. This includes the ability and creativity in using Learning media, both Learning media based on modern technology equipment and internet-based learning media. The use of social media is proven to help the learning process among the younger generation.This is in line with the purpose of the study. Namely to find the history and use of social media in supporting the learning process of Islamic religious education, it also reveals the Learning media for the younger generation is a technology-based learning media and learning media that is right for these people is social media that is very easily known by the younger generation and social media-based learning of Islamic religious education is also relevant in educating the younger generation today. This study uses qualitative research and library research approach. There are several types of social media that are a means to improve Islamic education learning, namely whatsapp, YouTube, kahoot and zoom meetings.